Validity and Reliability of a Non-invasive Test to Assess Quadriceps and Hamstrings Strength in Athletes - Mondin, Davide; Owen, Julian A.; Negro, Massimo; D’Antona, Giuseppe (Frontiers in Physiology, 2018)
Hamstring strains are one of the most frequent non-contact injuries in team sport, which fatigue and muscle imbalance have been found to be modifiable risk factors. The individual strength profile of hamstrings and quadriceps can predict hamstring injury risks. The aim of this study was to propose an easy new test alternative, that can test hamstring and quadriceps strength, using a traditional aneroid sphygmomanometer. Validity and reliability of the sphygmomanometer test were investigated at 30° and 90° of knee flexion for hamstring and quadriceps for both legs. 14 amateur athletes were tested with the sphygmomanometer test and with the isokinetic dynamometer, at 60°/s of speed, on the same visit, the best score obtained on three trials for each method, each leg and each angle were compared through Pearson’s correlation. For the reliability others 10 semi-professional rugby players were tested only with the sphygmomanometer test during two visits, with one week of difference, in their gym. The correlation between the visits were analysed using the Pearson’s correlation analysis. The sphygmomanometer test was found valid and reliable for hamstring strength evaluation at 30° (Validity: right PCC=0.574; left PCC=0.623) (Reliability: right PCC=0.865; left PCC=0.805) and at 90° (right PCC=738; left PCC=0.802) (Reliability: right PCC=0.717; left PCC=0.778). In conclusion, the present findings showed that the sphygmomanometer test is valid and reliable enough to analyze the strength of quadriceps and hamstring of semi-professional and amateur athletes.